Block error rate of optical wireless communication systems over atmospheric turbulence channels. Issue 5 (1st March 2014) - Zhang, Qian; Cheng, Julian; Karagiannidis, George K.
Abstract : Block error rate performance of subcarrier intensity modulation based optical wireless communication systems is analysed over Gamma–Gamma and lognormal atmospheric turbulence channels. The analysis is applicable to non‐coherent binary modulations and coherent binary phase shift keying. The special cases of K ‐distributed strong turbulence channel and negative exponential turbulence channel are also considered. The closed‐form expressions of block error rate in the Gamma–Gamma turbulence channels are derived using a series expansion of the modified Bessel function. For the lognormal turbulence channels, the Gauss–Laguerre quadrature method can be used to estimate the block error rate accurately.